(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
They are intrinsic to the extension of society from the local to a global level. By calling the economy human we put people first, making their thoughts, actions and lives our main concern. ‘Humanity’ is a moral quality of kindness and, since theoretical abstraction is impersonal, economic anthropology should pay attention to the personal realm of experience.